Universidades y promoción de la salud: ¿cómo alcanzar el punto de encuentro? Universities and health promotion: how can the two come together? - Mónica Muñoz (Revista Panamericana de Salud Pública, 2008)
Universities play a leading role in the communities in which they are found. Focused on leadership and developing knowledge, universities are the stage on which community members are formed. Through education, research, and by spreading knowledge, universities guide and support changes at the national and international levels. The university that advances health is one that joins health promotion with its purpose, aiming to foster human development and improve quality of life for its students and employees, thus impacting both the labor and social circles. It aspires to take a leading role in cultural change by raising awareness among the more educated, open, enterprising, and upstanding, and those committed to progress. This article's objective is to share a reflective analysis regarding the relationship between the university and health promotion in order to motivate and recommend action items to other universities advanced in this area. This analysis stems from experience gained over several years at the Pontificia Universidad Católica of Chile, through its health program, UC Saludable, in addition to a systematic review of the literature covering several years. The analysis develops four concepts that are central to all universities and that frame the health promotion effort: respond to health issues and educate the public; produce and disseminate health promotion knowledge; direct and support awareness of self-care and healthy lifestyles; and be a model change agent.